2022
DOI: 10.1039/d1ta10440c
|View full text |Cite
|
Sign up to set email alerts
|

CO2 electrochemical reduction on metal–organic framework catalysts: current status and future directions

Abstract: The versatility of MOFs is ideal for designing efficient CO2RR electrocatalysts, yet their poor stability and conductivity needs to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 122 publications
(160 reference statements)
1
32
0
Order By: Relevance
“…MOFs advanced electrochemical reduction of CO2 [281][282][283][284][285][286][287][288][289][290][291] and electro-carboxylation [292] .…”
Section: Electrochemical-based Methodsmentioning
confidence: 99%
“…MOFs advanced electrochemical reduction of CO2 [281][282][283][284][285][286][287][288][289][290][291] and electro-carboxylation [292] .…”
Section: Electrochemical-based Methodsmentioning
confidence: 99%
“…MOFs advanced electrochemical reduction of CO 2 [281][282][283][284][285][286][287][288][289][290][291] and electrocarboxylation. [292] Electrochemical CO 2 reduction reaction (CO 2 RR) is promising for CO 2 conversion to valuable chemical compounds.…”
Section: Hydrogenation For Comentioning
confidence: 99%
“…According to previous reports, there are many Cu-based materials to enhance the activity of the catalysts in CO 2 reduction, including oxide-derived Cu, Cu-based alloys, Cu single atoms, Cu-MOF materials, etc. Among these materials, MOF materials have been widely studied due to the high dispersion of metal sites and the tunability of ligands. In addition, numerous studies have found that the Cu-based nanoclusters of mixed Cu + /Cu 0 states are more favorable for the adsorption of CO 2 reduction intermediates, which can effectively convert CO 2 into C 2+ products. Recently, highly active Cu-based nanoclusters can be synthesized through the preactivation of MOFs containing Cu–O 4 nodes, which not only improves product selectivity but also greatly enhances the current density. For example, Cao’s group constructed the single-type Cu 2 O (111) site on CuHHTP by preactivation.…”
Section: Introductionmentioning
confidence: 99%